Structural study of liquid rare earth metals from charged hard sphere reference fluid - Thakor, P.B.; Gajjar, P.N.; Jani, A.R. (Condensed Matter Physics, 2002)
The present article deals with the investigation of structure factor, s(q) ; radial distribution function, g(r) and interatomic distance, r₁ of liquid rare earth metals, Nd, Dy, Ho, Er and Lu by adopting Charged Hard Sphere (CHS) reference fluid. To describe electron-ion interaction, our well established model potential along with the dielectric function due to Taylor is used. Good agreement between present and experimental findings is concluded. В даній статті вивчаються структурний фактор s(q) , радіальна функція розподілу g(r) і міжатомна відстань r₁ рідкоземельних рідких металів Nd, Dy, Ho, Er і Lu на основі флюїду заряджених твердих сфер. Для опису взаємодії електрон-іон використовується наш модельний потенціал разом з діелектричною функцією Тейлора. Робиться висновок про добре узгодження отриманих результатів з експериментальними.